Preliminary Design of a Catamaran Ship for Water Tourism in Lake Sunter - Augustinus Pusaka; Lurimarna Syahdan; Shanty Manullang; Ayom Buwono; Rizky Irvana (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Lake Sunter, an man-made lake built since the 1970s and covering approximately 33 hectares, is commonly referred to as Lake Podomoro. Positioned as an urban recreational space, its scenic vistas offer potential for diverse water-based activities. In order to increase tourist engagement with the lake, it is imperative to diversify the available attractions. Among these attractions, tourist boats emerge as a viable option to capture public interest. Accordingly, this study attempts to design a catamaran tour boat equipped with motorcycle propulsion, tailored for operation on Lake Sunter. In the first stage, the primary dimensions of the catamaran vessel are determined using the linear regression method, resulting in dimensions of L = 3.2m, H = 1.15m and T = 0.4m, with a passenger capacity of 3 persons. The ship's stability is then assessed in accordance with the criteria of the IMO A.749 (18) Code On Intact Stability, Chapter 3, which applies to all ship designs. This assessment includes Load Case I and Load Case II conditions to determine the stability of the ship under different scenarios.